The Reconfiguration of Kaduna Municipal Area Distribution Network For Power Loss Reduction And Voltage Profile Improvement Using Static Var Compensators (SVC) - Airoboman , Abel Ehinem; Alhaji Bukar, Bukar; Araga, I.A (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2025)
Increase in demand for electricity due to the advancement of technology globally and in Nigeria has brought about numerous challenges such as voltage instability, power factor problems and high power loss in the electrical power distribution networks. This paper presents a Static Var Compensator (SVC) placement on the power distribution network of Town One Station Kaduna, Nigeria, to investigate its impact on improving the network’s voltage profile and reducing the active power loss in the system. For analysis, the bus voltage, power, and the current passing through the chosen feeders were measured and noted appropriately. The network parameters which include route length, transformer parameters and the maximum power flow were obtained from Kaduna electricity Distribution Company, Kaduna, Nigeria. The distribution network was modelled and simulated in ETAP software environment, for both with and without Static Var Compensator (SVCs). The results obtained from the simulation indicated that buses 5, 7, 8, and 47 others has voltage magnitude of 0.745 – 0.932pu which are clearly outside acceptable limit of 0.95 – 1.05Pu. Further result showed real and reactive power loss of 8527 kW and 23535 kVAr is experienced by the network. After the SVCs placement, the power loss reduced from 8527 kW to 6751 kW and minimum system voltage improved from 0.745 – 1.02 Pu.